Survey of Internal Parasites of Buffalo Calves and Calves in Buri Ram and Surin Province - Sathaporn Jittapalapong; Yanyong Intraraksa; Nongnuch Jantaraj; Khampee Phatthanathanang (Agriculture and Natural Resources, 1993)
Fecal samples of buffalo calves and calves in Buri Ram and Surin province were examined by Formalinether sedimentation during June-July 1990, Infestation rates of internal parasites of calves in Buri Ram and Surin province were 33.33% and 43.64% respectively. Infestation rates of internal parasites of buffalo calves in both provinces were 42.53% and 43.94%, respectively. Rumen fluke, Toxocara vitulorum and Strongyloides papillosus were the most prevalent parasites in this study.